Pricing practices of Ar-Rahnu providers in Malaysia - Nik Azman, Nik Hadiyan; Kassim, Salina (Inderscience Enterprises Ltd., 2017)
Ar-rahnu is a shariah-compliant pawnbroking instrument that has high suitability to serve short-term and immediate financial needs of the lower income people. An important component of ar-rahnu is the safe-keeping/service fee on the collateral items charged by the ar-rahnu providers. This study highlights the pricing practices of selected ar-rahnu providers in Malaysia by comparing the service charges that they imposed as well as the loan margins granted by each of the providers. By doing so, the study aims to provide a critical discussion on the related issues arising from the pricing practices. This study hopes to shed lights on the role of ar-rahnu in providing inclusive financing to the low income group. Findings of this study contribute towards better growth of the ar-rahnu industry in particular, and the Islamic finance industry in general.